2015
DOI: 10.1007/s10610-015-9282-x
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of Safety In The Presence Of the Police, Security Guards, and Police Volunteers

Abstract: Uniformed presence is commonly thought to create feelings of safety in people. However, do differently uniformed people contribute to an equal amount of safety and are there situation-dependent differences? The present study examined the association between various types of uniformed presence and people's feelings of safety through a questionnaire among 352 respondents (18-86 years) (49.1 % women). The questionnaire contained pictures of situations perceived as relatively safe and unsafe with or without unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Further, as results are grounded in real-life role orientations among PVR officers, the four identified in this study may be used by the RMP administration in policy planning and implementation. For example, as we noted above, Doyle et al (2016, p. 19) found that police volunteers may be a cost-effective alternative in some social situations. This implies that, for example, PVR officers’ roles as ambassadors may be utilized when situations call for the presence of a uniformed body resulting in enhanced public confidence.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Further, as results are grounded in real-life role orientations among PVR officers, the four identified in this study may be used by the RMP administration in policy planning and implementation. For example, as we noted above, Doyle et al (2016, p. 19) found that police volunteers may be a cost-effective alternative in some social situations. This implies that, for example, PVR officers’ roles as ambassadors may be utilized when situations call for the presence of a uniformed body resulting in enhanced public confidence.…”
Section: Discussionmentioning
confidence: 72%
“…They found that “while both groups in the study are confident in their professional ability to handle issues at a policing scene, UK volunteer officers feel less confident about interviewing and administrative paperwork than their US counterparts” (Wolf et al , 2017, p. 24). Researching feelings of safety among members of the public engendered, in turn, by regular police, security guards and police volunteers, Doyle et al (2016, p. 19) found that “in situations perceived as relatively unsafe […] all types of uniformed presence increased feelings of safety” and that “security guards and police volunteers created similar amounts of feelings of safety making police volunteers a cost-effective alternative” for police agencies. In the sparse research on police volunteers discussed, almost no elucidation of their occupational roles exists, especially as perceived and elaborated on personally and reflexively.…”
Section: Police Roles and Volunteerismmentioning
confidence: 99%
“…In terms of security features, well-designed measures such as fences, locks, or secure entry systems have the potential to reduce fear of crime, whereas evidence is limited for closed-circuit television (CCTV), multicomponent environmental crime prevention programs, or regeneration programs (80). Perception of safety may be influenced by the presence of uniformed security guards but only in situations when safety is perceived to be inadequate without them (43). After enhanced security measures were introduced into Liverpool, tower block buildings in the United Kingdom, fear of domestic crime was reported as being much lower among residents relative to the greater population of Britain.…”
Section: Safety and Securitymentioning
confidence: 99%
“…Although this change was initially well received by the public, police officers were subject to higher rates of physical assault while wearing the alternative uniforms; it was not until the former uniforms were reinstated that these incidents returned to their average quota (Johnson, 2013;Johnson et al, 2015). Correspondingly, when exploring public perceptions of uniforms worn by police officers and police volunteers, research shows that not only do more members of the public successfully identify a police officer in contrast to a police volunteer (Rowland and Coupe, 2014), but also that members of the public feel safer in the presence of police officers than police volunteers (Balkin and Houlden, 1983;Doyle et al, 2016;Rowland and Coupe, 2014).…”
Section: Police Volunteer Uniformsmentioning
confidence: 99%